Toward a behavioral approach of international shipping: A study of the inter-organisational dynamics of maritime safety - François Fulconis; Raphael Lissillour (Journal of Shipping and Trade (JST), 2021)
Classification societies play a major role in maritime safety and the regulation of the international shipping market. They have a dual mission, namely the classification and certification of ships. Paradoxically, the academic literature on the strategic behaviour of classification societies remains very limited. More often than not, the scope of prior research has been limited to the definition of their missions in the shipping ecosystem with an emphasis on their changing legitimacy as maritime accidents occur. Consequently, this paper aims at providing a better understanding of the specific role of classification societies in maritime safety and within the inter-organisational dynamics of international shipping. The study is based on a conceptual framework provided by the behaviourist approach and applied to the inter-organisational dynamics of supply chains. This approach enables in-depth analysis of actors' strategic behaviours by focusing on four dimensions: power, leadership, conflict and cooperation. The main results highlight the increasingly central and paradoxical role of classification societies. This role encompasses, on the national level, classification and certification processes, and, on the supranational level, the creation of new rules and regulations. The study highlights the importance of their ability to master the official framework and institutional vocabulary, which enable them to strengthen their power and leadership in the shipping market. This capacity helps them to limit conflicts between actors and to encourage certain cooperative behaviours based on relationships of dependence and inter-organisational interdependence.
Keywords: 650; Behaviourism; Classification societies; International shipping; Maritime safety